Scientific Approach in K-13; the Impact on the Quality of the Learning Process and Outcomes in MAN (Program Studi Pendidikan Agama Islam, 2020)
The Kurikulum 2013 –Indonesia's novel Curriculum invented in 2013– is implemented through activity-based learning using a scientific approach. Curriculum changes do not only occur in the dimensions of the plan/document, but in its implementation in the quality of the process which has an impact on learning outcomes. This research aims to determine the implementation of the Kurikulum 2013 scientific approach and its impact on the quality of the learning processes and outcomes at MAN in Lampung Province. The research uses a mixed methods with sequential mixed methods design. The respondents consisted of 26 teachers and 126 students. Data were collected by conducting interview, observation, documentation, and questionnaire. The validity was tested by Pearson’s validity and Cronbach Alpha reliability. The results showed that teachers can apply a scientific approach to the implementation of the Kurikulum 2013 well. It can be seen from the teacher’s ability to prepare lesson plans, though there are some teachers (working period of 21 to 30 years) who are constrained during the learning process, such as observing the learning and not being able in presenting the media. The scientific approach has a very good impact on the quality of the learning process and outcomes. It can be seen by the increase in student learning outcomes.